Calculation of the Mobile Phone Radiation Level in Respect to the Exposure Standards - Al-Bazzaz, Sabah Hawar Saeid (University of Science and Technology, Sana'a, 2008)
The widespread use of mobile phones is a recent phenomenon. Mobile phones produce radio-frequency radiation that is part of the electromagnetic radiation spectrum. It is the only radiation producing consumer product that people intentionally place against their head for extended time periods. There is irrefutable evidence that mobile phone radiation affects biological mechanisms in the body. This radiation penetrates the head and increases the brain temperature (thermal level) of the user while the phone is in use, also affects protective biological mechanisms in the body. Since the large amount of general population is using the mobile phones, there is a need to determine the level of radiation in respect to the exposure standards. The purpose of this paper is to calculate the radiation power density of mobile phone and find out how mobile phone radiation decreases over short and long distances, as well as if using a mobile phone in a public place is similar to second-hand smoke.